Clinical features of omicron SARS-CoV-2 variants infection associated with co-infection and ICU-acquired infection in ICU patients - Li, Dong-Jie; Zhou, Can-Can; Huang, Fang; Shen, Fu-Ming; Li, Ying-Chuan (Frontiers in Public Health, 2024)
Background Although the decreasing rate of hospital admission in the omicron wave has led countries to loosen control, still the patients requires ICU admission. It is common for viral respiratory infections to be co-infected with bacteria. However, the difference between co-infection and ICU-acquired infection on their clinical characteristics and outcomes during the Omicron wave was little reported. Methods Clinical and microbiological data were collected from ICU patients with omicron infection between April 1st, 2022, and May 31th, 2022 and a comprehensive comparative study of the clinical characteristics and endpoint were conducted. Results The Omicron SARS-CoV-2 variants-infected patients requiring intensive care had high rates of co-infection (42.55%). Additionally, the ICU COVID-19 patients with co-infection showed more severe clinical features compared to those with ICU-acquired infection. Furthermore, Multivariate Cox analysis demonstrated that co-infection (hazard ratio: 4.670, p = 0.018) was a significant risk factor for poor outcomes in ICU patients with COVID-19. Besides, Kaplan–Meier survival curve analysis revealed that COVID-19 patients with co-infection had a significantly shorter 28-Day survival time compared to those with ICU-acquired infection (p < 0.001). Finally, our investigation identified a significant association between the presence of Candida app. in the broncho-alveolar lavage and an elevated risk of mortality (OR: 13.80, p = 0.002) and invasive ventilation (OR: 5.63, p = 0.01). Conclusion Co-infection is prevalent among patients requiring intensive care and is linked to unfavorable outcomes in the Omicron wave. Consequently, more attention may be needed for the empirical antibacterial treatment in ICU patients within the COVID-19 Omicron variant, especially anti-fungi.